2015
DOI: 10.5414/cn108409
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum leptin levels are associated with good nutritional status in non-obese chronic hemodialysis patients

Abstract: Elevated serum leptin levels seem to be associated with good nutritional status. However, there was no correlation between leptin and inflammatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, low serum leptin levels predicted mortality in HD patients 42 . Elevated serum leptin levels were associated with good nutritional status in non-obese chronic HD patients 43 . In the present study we found a significant negative correlation of serum Alb, a nutrition marker, with serum lnleptin/BMI in controls.…”
Section: Discussionmentioning
confidence: 96%
“…However, low serum leptin levels predicted mortality in HD patients 42 . Elevated serum leptin levels were associated with good nutritional status in non-obese chronic HD patients 43 . In the present study we found a significant negative correlation of serum Alb, a nutrition marker, with serum lnleptin/BMI in controls.…”
Section: Discussionmentioning
confidence: 96%
“…Dervisoglu et al reported a negative correlation between serum leptin level and MIS . Kara et al separated patients without obesity who were undergoing MHD into three groups according to serum leptin level and determined that patients with high serum leptin levels had higher albumin and prealbumin levels and greater total iron binding capacity but significantly lower MIS . The results of a study conducted by Koo et al revealed positive correlations between serum leptin level and normalized protein catabolic rate, subjective global assessment score, triceps skinfold thickness, subscapular skinfold thickness, and mid‐arm muscle circumference, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that leptin potentially acts as a uremic toxin by contributing to the cachexia of uraemia . In contrast, other studies have reported a positive association between serum leptin levels and nutritional status in patients on maintenance hemodialysis (MHD) …”
Section: Introductionmentioning
confidence: 99%
“…Kara et al ( 8 ) reported association of elevated serum leptin levels with good nutritional status in non-obese chronic HD patients. However, similar to our findings no correlation between leptin and inflammatory status was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, numerous studies have demonstrated that HD patients with lower Body Mass Index (BMI) have higher relative mortality risk ( 7 ). Kara et al ( 8 ) recently reported negative correlation between increased leptin levels and lower malnutrition inflammation score which remained significant even after adjustments for BMI. However, significance of hyperleptinemia as well as its associations with inflammatory and nutritional status in HD patients is far from being fully elucidated.…”
Section: Introductionmentioning
confidence: 97%